One-Pot Green Synthesis of Strontium and Zirconium Nanoparticles: An In-vitro Study of their Antioxidant and Cytotoxic Activity - Kishorwara Ramamoorthy; T N Uma Maheswari; Saravanan Muthupandian; Devika S Pillai (Journal of Clinical and Diagnostic Research)
Introduction: The one-pot synthesis approach for Strontium and Zirconium Nanoparticles (Sr-Zr NPs) utilises pomegranate (Punica granatum) extract as a natural reducing and stabilising agent. This eco-friendly approach leverages the high antioxidant content of pomegranate to eliminate the need for toxic chemicals in nanoparticle production. Aim: To synthesise zirconium and strontium nanoparticles from the extract of Punica granatum and to assess their antioxidant and cytotoxic properties. Materials and Methods: The present in-vitro study was carried out in the Laboratory, Department of Pharmacology, Saveetha Dental College and Hospitals, Chennai, Tamil Nadu, India over a period of six months from November 2023 to May 2024. Pomegranate peel aqueous extract was prepared by drying and grinding the peels, followed by autoclaving, heating, and centrifugation to extract bioactive compounds. Zirconium and strontium nanoparticles were synthesised by mixing the extract with zirconium chloride and strontium chloride solutions, followed by continuous stirring. The formation of nanoparticles was confirmed by a colour change. The nanoparticles were characterised using Fourier Transform Infrared Spectroscopy (FTIR) and UV-visible Spectroscopy (UV-Vis). Their antioxidant efficacy was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPHH) assay, while cytotoxicity was evaluated using cell viability assays. Results: The synthesised Sr-Zr NPs were characterised by their structural and optical properties, exhibiting distinct UV-Vis absorption peaks at 286 nm and 371 nm. At the highest concentration tested (100 μg/mL), Sr-Zr NPs exhibited approximately 89% inhibition, whereas L-ascorbic acid showed 92% inhibition, demonstrating the potent antioxidant activity of the nanoparticles. The IC50 value, representing the concentration at which 50% of the cells were inhibited, was determined to be 90 μg/mL. At this concentration, cell viability was reduced to approximately 50%, indicating significant cytotoxic activity. Conclusion: The study highlights the potential of Sr-Zr NPs for biomedical applications, particularly in antioxidant therapies and cancer treatment, due to their potent biological activities and favourable optical properties. The use of pomegranate extract not only enhances the biocompatibility of the nanoparticles but also aligns with sustainable development goals, offering a promising pathway for the green synthesis of biocompatible nanoparticles with therapeutic potential.